Experiências formativas de uma escola pública bilíngue para surdos em curso médio normal - Pires, Cleidi Lovatto (2021)
This thesis was conducted at the Post-Graduate School of Education in the State University of Santa Maria, in the research field of Special Education, Diversity and Inclusion and has its main objective to comprehend the formative experiences being implemented to the establishment of deaf teachers in a Normal High School. The specific goals are: be acquainted of the teachers’ formative experiences when teaching in a Normal High School course; identify in the narratives of deaf students the development of formative experiences; understand how the job of being a deaf teacher has been constituted. The proposition affiliates to the theoretical-methodological field of a post-structuralist perspective in education, where I navigated through the experience concepts of Larrosa’s, and Masschelein and Simons regarding school. These concepts were applied taking into consideration the production of data from a deaf school in the Public State education in Santa Maria, Rio Grande do Sul. The methodological atmosphere of work constitutes from the notion of auto-ethnography and the production of the analytical materiality resulted from a group of data: official documents and narratives of teachers and students that were produced in pedagogical workshops. The first group of materiality is composed by the Political Pedagogical Project of the school; scholar regiment and curricular matrix. Beyond this, I added other documents related to deaf education and to the Normal High School organization from the State of Rio Grande do Sul. The second group was composed of the participation of four students and eight teachers from the course. The record of the materiality of the research happened through footage, photographies and field notes. From the analytical documental enterprise, which gave problematic clues to the research, it was possible to understand that the proposition of the school is based in a bilingual education, where the Brazilian Sign Language is the first language of the institution. From this linguistic centrality, it was possible to notice a methodology focused in visuality. Such documents support that an education ruled in deaf singularities exists, and that the formation of teachers is anchored in a bilingual perspective. However, as a result of the workshops with the students and teachers, it became evident that there are other concerns in the school context that are very much about what a school is and what makes a school a school. Such elements talk about planning, interdisciplinarity, the act of play and about the importance of the teacher being a moving archivist in its pedagogical action, through where is possible to produce pedagogical experiences meanwhile in action. There is a lot of school in this deaf school, however, it also has its uniqueness due to having Sign Language present. The Sign Language composes the scholar context and it is a strong discursive scorer, with a power to instigate a decolonized movement of existing and resisting in the school. In this regard, the scholar seeks the Normal High School course much more as a strengthening of such movement instead of seeking the profession of becoming a deaf teacher.